Collaborative Governance to Prevent Child Sexual Abuse in Bogor Households - Wira, Ariski; Silitonga, Mala Sondang (Journal of Law, Politic and Humanities, 2025)
This study examines collaborative governance strategies in preventing child sexual abuse within household settings in Bogor Regency. The increasing rate of child sexual violence indicates weaknesses in protection systems and suboptimal coordination among stakeholders. Collaboration among local governments, educational institutions, law enforcement, civil society organizations, and families is the primary focus of this research. A qualitative approach was employed to explore the dynamics and effectiveness of inter-actor collaboration in addressing the complexity of child abuse. The Ansell & Gash collaborative governance model serves as the analytical framework, encompassing initial conditions, institutional design, facilitative leadership, and collaboration processes. Findings reveal that existing collaborations are not yet fully integrated, hindered by low public awareness, weak intersectoral coordination, and unequal access to rehabilitation and reporting services. Proposed prevention strategies include institutional capacity strengthening, establishment of formal coordination mechanisms, and enhancement of community literacy on child sexual violence. These findings offer significant contributions to collaborative governance practices in addressing complex social issues and provide a replicable model for regions with similar characteristics